1999
DOI: 10.1074/jbc.274.33.22999
|View full text |Cite
|
Sign up to set email alerts
|

The p67 Activation Domain Regulates Electron Flow from NADPH to Flavin in Flavocytochromeb 558

Abstract: An activation domain in p67phox (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
146
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 53 publications
(50 reference statements)
7
146
0
3
Order By: Relevance
“…These findings support a pivotal role for p67 phox in oxidase activation, a concept that was strengthened by the definition of an "activation domain" in p67 phox , consisting of residues 199 -210 (21) or 187-210 (22). This domain was proposed to interact with gp91 phox and to control electron flow from NADPH to FAD (23). Experimental evidence for this was recently provided by the findings that p67 phox binds to gp91 phox (24) and that Rac1 (24) and phosphorylated p47 phox (25) increase the binding of p67 phox to cytochrome b 559 .…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…These findings support a pivotal role for p67 phox in oxidase activation, a concept that was strengthened by the definition of an "activation domain" in p67 phox , consisting of residues 199 -210 (21) or 187-210 (22). This domain was proposed to interact with gp91 phox and to control electron flow from NADPH to FAD (23). Experimental evidence for this was recently provided by the findings that p67 phox binds to gp91 phox (24) and that Rac1 (24) and phosphorylated p47 phox (25) increase the binding of p67 phox to cytochrome b 559 .…”
mentioning
confidence: 60%
“…A model of oxidase activation has been put forward (21,23,26) in which p67 phox functions as the "activator," whereas p47 phox and Rac serve as "organizers," in agreement with the recently adopted nomenclature of p67 phox and p47 phox homologues. To better understand the distinct organizer roles of p47 phox and Rac, we designed a cell-free activation system consisting of prenylated (geranylgeranylated) Rac1, which represents the physiological form of Rac1 in eukaryotic cells, phagocyte membranes, and p67 phox (26).…”
mentioning
confidence: 98%
“…The Rac Switch I domain in its GTP-bound form interacts with the tetratricopeptide repeat of p67 phox (36), a direct activator of the NADPH oxidase (43). The crystal structure of the Rac-p67 phox complex revealed that Ala 27 and Gly 30 of Rac are crucial to the stability of this assembly (36).…”
Section: Discussionmentioning
confidence: 99%
“…An allosteric regulation mechanism was suggested in which p47 phox behaves as a positive effector that increases the affinity of p67 phox for cytochrome b 558 (53,54,11). In vivo, phosphorylated p47 phox serves as an adapter protein bringing p67 phox into proximity with flavocytochrome b 558 (55).…”
Section: Discussionmentioning
confidence: 99%